Perceptions of the New Role of the Research Champion in Developing a New ITE Partnership: Challenges and Opportunities for Schools and Universities. (1st March 2020) - Pugh, Ceri; Thayer, Emma; Breeze, Thomas; Beauchamp, Gary; Kneen, Judith; Watkins, Sharne; Rowlands, Bethan
After a process of competitive tendering for the provision of initial teacher education in Wales, there is an opportunity to re-examine the relationship between schools and universities. With the growing importance of research for both student and serving teachers, the Cardiff Partnership developed a model where a school-based 'Research Champion' (RC) would be an integral part of the support for capacity building and developing excellence. Although this model has previously been used in different forms at Oxford and Manchester Universities, the role was new to schools in the Cardiff Partnership. Semi-structured one-to-one interviews were conducted with a representative sample of RCs in primary and secondary schools and university staff to reflect on the challenges and opportunities in the early stages in developing this unique role in the context of an evolving education context in Wales. This study uses data from these interviews to establish key ideas around the emerging role of the RC, the shift in working relationships between schools and universities and what is needed to bridge the gap between research and practice. Interviews were transcribed and, after open-ended thematic analysis, opportunities and challenges are reported. These themes include: bridging the gap between educational research and classroom practitioners; types of knowledge drawn upon by teachers; changes in role and identity. Suggestions for further research monitoring the ongoing development of the role are suggested.